Peran Citra Merek, Persepsi Harga, Persepsi Risiko Terhadap Minat Beli Produk Smartphone Merek Xiaomi - Ende Ende; Jaka Wijaya Kusuma (Sains: Jurnal Manajemen dan Bisnis, 2017)
This study examined the effect of the brand image, perceived price, and perceived risk on purchasing intention. Samples numbered 62 people who intend to buy a Xiaomi smartphone. The population is number of the fifth-semester management economics students of the private economics institute in Bandung. Multiple regression analysis is a statistical method chosen to explore the observed variables. The results showed that the brand image and perceived risk is not significant influence purchase intention. Meanwhile, the perceived price significantly influences to purchase intention.